A Brief Overview of Stereology and Morphometry Method in Histology and Biology - Tuğba Dağdeviren; Hatice Kübra Yolcu (Turkish Journal of Agriculture: Food Science and Technology)
Quantitative analyses in biological science are especially important in terms of determining and comparing the geometric properties of biological structures. Stereology and morphometry are two important complementary methods frequently used in this field. Stereology refers to the quantitative analysis of the three-dimensional geometric properties of biological structures. In particular, it is used to determine the criteria such as volume, surface area and length of many cells, organelles and tissues with microscopic properties. In addition, this method allows to obtain information about three-dimensional structures by measurements made on randomly selected sections. Thanks to these techniques, accurate estimates of the general structure can be made with data obtained from certain sections instead of examining biological samples completely. Morphometry, on the other hand, is suitable for examining biological structures in terms of shape and size. It is a suitable method for determining the shape changes of organisms and structural elements. Morphometry digitizes the data by making measurements in the digital environment and performs statistical analysis on these data. Measurements are made more quantitative by volume fraction analysis. The importance of stereology and morphometry in quantitative morphology enables the objective realization of biological structures in quantitative analysis in both methods. These methods thus allow the examination of the material at hand, which is mathematical and statistical. In addition to biology, tissue science Quantitative biology has a special place in three-dimensional studies in histology. This review is particularly concerned with stereology and morphometry, and the aim of the review is to give dimension to a specific topic under investigation, thus providing a good background for diagnostic decision making by strengthening traditional approaches, and to address the contributions of these methods in scientific studies.